Subcorneal Pustular Dermatosis: A case report of a patient with diffuse scleroderma (Community Based Medical Journal, 2022)
Subcorneal pustular dermatosis (SPD) or Sneddon-Wilkinson infection is an uncommon, harmless, constant, sterile pustular ejection which is related with different foundational sicknesses including immunoglobinopathies, neoplasms, and immune system issues. This paper reports an instance of SPD in a patient with diffuse scleroderma in a 37-year-elderly person. The speculation that invulnerable dysregulation might assume a part in the pathogenesis of SPD was assumed by the concurrence of diffuse scleroderma and SPD in our patient.CBMJ 2021 January: vol. 10 no. 01 P: 50-53